Physical and genetic characterization of the genome of Lactobacillus lactis bacteriophage LL-H. - Trautwetter, A (1986)
Bacteriophage LL-H is a virulent phage of Lactobacillus lactis LL23. A restriction map of the phage genome was constructed with various restriction endonucleases. This chromosome has a 34-kilobase size and seems to be circularly permuted. We used a bank of LL-H restriction fragments to study the expression of five of the seven main phage particle proteins. Immunoblotting experiments permitted the mapping on the chromosome of several genes coding for phage particle proteins. We also show that the gene of the main capsid protein is expressed from its own promoter in an Escherichia coli strain.